Towards a cleaner CHO chassis: systematic knockout of host cell proteins for efficient biopharmaceutical manufacturing - Marzluf, Jannis Peter; Klein, Jennifer; Kirchmeier, Daniela; Stärk, Alexander; Ziegner, Daniel; Gehrung, Markus; Rauh, Franziska; Rattay, Merle; Zehe, Christoph; Leroux, Ann-Cathrin (Frontiers in Bioengineering and Biotechnology, 2026)
Host cell proteins (HCPs) are major process‐related impurities in biopharmaceutical manufacturing, imposing metabolic burden on production hosts and complicating downstream purification, thereby impacting cost, product stability, and patient safety. Here, we engineered Chinese hamster ovary (CHO) cells toward a streamlined production chassis through multiplex CRISPR‐mediated knockout of abundant and difficult‐to‐remove HCPs. Proteomic profiling across multiple clones, products, and downstream purification steps identified a core set of highly abundant proteins that contributed disproportionately to total released HCP mass and showed limited removal by standard purification processes. Screening of 62 candidate genes using pooled and single‐cell knockout approaches identified targets compatible with cell growth and productivity, yielding 36 validated candidates suitable for host‐cell streamlining. Multiplex editing of selected targets achieved approximately 57–85% reduction in released HCP levels, depending on configuration, without compromising growth, viability, or productivity in fed‐batch cultures. The resulting cell lines maintained bioprocess performance while substantially lowering impurity load. Together, this work demonstrates a scalable, proteomics‐guided strategy for rational host‐cell engineering that enables upstream reduction of persistent impurities and supports cleaner, safer, and more cost‐efficient biopharmaceutical manufacturing.